Sociodemographical characteristics associated with adherence to treatment in adults with type 2 Diabetes - Cordero-Sánchez, Clemente; Alba-Alba, Corina; Muñoz-Covarrubias, Madai; Guzmán-Ortiz, Elizabeth; Ramirez-Giron, Natalia (Horizonte Sanitario, 2022)
Objective: To establish the association of sociodemographic characteristics and treatment adherence in Mexican adults with Type 2 Diabetes.Materials and Methods: A descriptive, cross-sectional study was made in Mexican adults over 18 years with Type 2 Diabetes who attended a diabetes clinic of a public hospital. The sample were 100 adults. Conscious adults, diagnosed with DT2, with a minimum evolution of three years with the diagnostic were included. The Morisky, Green and Levine´s test was used to identify the adherence to the treatment.Results: The female sex predominated (62%), the adults between 50-59 years were the most representative group (59%); el 46% had primary school and 69% were married. The 23% of the sample has 3 years with the diagnostic, only 38% of the respondents do exercise 10-15 minutes a day and 28% did not do exercise; the majority report having a pharmacological treatment based on oral hypoglycemic agents (82%). The age was associate with the adherence to the treatment (p